Synergism between membrane gangliosides and Arg-Gly-Asp-directed glycoprotein receptors in attachment to matrix proteins by melanoma cells (The Rockefeller University Press, 1988)
The identification of specific cell surface glycoprotein receptors for Arg-Gly-Asp-containing extracellular matrix proteins such as fibronectin has focused attention on the role of gangliosides in this process. Is their involvement dependent or independent of the protein receptors? In attachment assays with cells from a human melanoma cell line, titration experiments with an antibody (Mel 3) with specificity for the disialogangliosides GD2 and GD3, used together with a synthetic peptide containing the cell binding sequence Arg-Gly-Asp, show that their joint effect is synergistic. Both the Mel 3 antibody and the synthetic peptide individually cause rapid detachment of melanoma cells from fibronectin substrate but, when used together, much smaller concentrations of both are required to achieve the same effect. The Mel 3 antibody was not nonspecifically reducing receptor binding to the Arg- Gly-Asp sequence since, in binding assays with radiolabeled peptide performed with cells in suspension, very little peptide is bound by the melanoma cells under these conditions but addition of Mel 3, an antibody of IgM isotype, causes a two- to threefold increase in specific binding. The simplest interpretation of these data is that the Mel 3 antibody is causing sufficient clustering of membrane gangliosides in local areas and producing a favorably charged environment to facilitate peptide binding by specific glycoprotein receptors.